Voice of women's freedom: Women’s perspective through movie Before, Now & Then (2022) - Agani, Afinada Aulia; Lukmantoro, Triyono (Universitas Bunda Mulia, 2024)
The movie Before, Now & Then (2022) raises the theme of Nana's life history as she breaks away from patriarchal hegemony through women's perspectives. Inspired by director Kamila Andini's anxiety about the role of women in movies, she invites the audience to experience the story from a woman's perspective. This study aims to analyze the voice of women's freedom from the female gaze through the movie Before, Now & Then (2022) using Baudrillrad's simulacra method and a postcolonial perspective. This approach seeks to uncover the colonialism practices behind the movie as a superstructure of power, providing a basis for analyzing the movie. The main female character is portrayed as someone who speaks little but takes decisive action to liberate herself from patriarchy by using women's language and point of view. The movie’s storyline focuses more on the life story of Nana to escape from the patriarchal restraints inherent in people's lives, especially since the movie's storyline was in the post-ideological war West Java in 1960. The study concludes that this movie can depict women’s perspectives through its characterization and storyline.